PRODUKTIVITAS TENUN SONGKET DALAM MENINGKATKN PEREKONOMIAN KELUARGA DI DESA TALANG PANGERAN ULU KECAMATAN PEMULUTAN BARAT KABUPATEN OGAN ILIR - Imaniar Imaniar; Eva Susanti; Novita Sari; Msy. Mikial (JURNAL KOMPETITIF, 2022)
This research is motivated by the author's curiosity about the Productivity of Songket Weaving in Improving the Family Economy in Talang Prince Ulu Village, West Pemulutan District, Ogan Ilir Regency. This study aims to find out about the productivity of songket weaving and the family economy in Talang Prince Ulu Village, West Pemulutan District, Ogan Ilir Regency. This study uses a qualitative approach that is descriptive and uses an inductive analysis approach. The source of the data in this study were the songket weaving craftsmen of Talang Prince Ulu Village with a total sample of 25 people. Data collection techniques using observation and interviews. While data analysis techniques with data reduction, data presentation, conclusions and verification. The results of the Productivity Research on songket weaving in Talang Prince Ulu Village, West Pemulutan District, Ogan Ilir Regency use several productivity methods, including choosing the right songket motif, choosing high-quality yarn, working hours and the age of productive craftsmen. The family economy in Talang Prince Ulu Village, West Pemulutan District, Ogan Ilir Regency, from the results of songket weaving varies widely in terms of income ranging from IDR 1,000,000 to IDR 2,250,000. Songket weaving craftsmen in Talang Prince Ulu Village, West Pemulutan District, Ogan Ilir Regency should further improve their understanding and knowledge in terms of songket weaving productivity so that the income level of songket weaving craftsmen increases and the family economy is even better. It is also hoped that the government should increase the intensity of outreach to songket woven craftsmen to increase the knowledge of craftsmen on how to produce high quality songket cloth, so that it has a high selling value for the family economy.Keywords: Productivity, Songket Weaving, Family Economy